INSTRUCTIONAL DESIGN USING THE LEE & OWENS MODEL FOR DEVELOPING AN EFL LEARNING SUPERVISION SYSTEM IN MADRASAH ALIYAH - Anwar; Saharudin; Sofyan (Indonesian EFL Journal, 2026)
This research investigates the application of the Lee & Owens instructional design model for developing a digital English language learning supervision system in Madrasah Aliyah. The study follows the five-phase model, which includes Analysis, Design, Development, Implementation, and Evaluation, to create a system that meets both pedagogical needs and technical requirements. Data were collected through interviews, surveys, and document analysis, and the design process was informed by comprehensive needs analysis. The system underwent expert validation and user testing, with formative evaluations integrated throughout the development cycle. The results indicate that the Lee & Owens model effectively guided the development of a user-centered, pedagogically sound system. Expert validation and high user satisfaction confirmed the system's practicality and effectiveness in enhancing English language learning supervision. This study demonstrates the importance of a structured, iterative, and user-centered approach in developing educational technology solutions for language learning in Madrasah Aliyah.